Genetic structure and climate niche differentiation among populations of Leopardus geoffroyi - Fameli, Alberto Francisco (2024)
Geoffroy's cat (Leopardus geoffroyi) is a small-sized felid native to South America. Given the species'distribution covering a wide variety of habitats, and the presence of high levels of anthropization in part of its range, it is possible that genetically differentiated groups exist and that they occupy different climatic niches. We assessedpatterns of contemporary genetic diversity and structure in the species across most of its range, characterizing each inferred genetic group based on ecological nichemodels. We genotyped 11 microsatellites for 142 samples covering most of Geoffroy's cat distribution, and investigated patterns of genetic structure and diversity, applying spatial and nonspatial Bayesian clustering methods and a spatial principal component analysis. We created ecological niche models for each genetic cluster, evaluating whether theseclustersoccupy different climatic spaces and display differences in the suitability of different values of the climatic variables analyzed. We identified two geneticclusters, one in the north-northeast and the other in the south-southwest of the species' distribution. These clustersshowed moderate FST values between them and differences in dispersal/genetic diversity. We found isolation-by-distance patterns globally and within each cluster. We observed lower expected heterozygosity compared with other studies and a north–south gradient in allelic richness. The southern cluster showed lower genetic variability and a more restricted climatic niche suggesting that this group is morevulnerable to the effects of the current context of climate change. Individuals from the southern genetic cluster are under different pressures, likely a product of the particularly dry habitat they occupy. Climatic variables associated with habitat suitability suggest the southern cluster has affinity for the arid and semiarid conditions resent in its distribution. Conservation measures should consider the genetic structure observed and differences in climatic spaces tomaintain the evolutionary potential of the species.